Who s for coffee? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
How far can the coffee price fall? In early September 2001, it stood at an all-time low of US$ 0.41 per pound and the trade media were abuzz with the question 'Why is nothing being done?'. The fall started in 1989 when the USA, consumer of half the...